2017
DOI: 10.1007/s11307-017-1122-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Biodistribution of Radiolabeled Acoustic Protein Nanostructures

Abstract: Purpose Contrast-enhanced ultrasound plays an expanding role in oncology, but its applicability to molecular imaging is hindered by a lack of nanoscale contrast agents that can reach targets outside the vasculature. Gas vesicles (GVs)—a unique class of gas-filled protein nanostructures—have recently been introduced as a promising new class of ultrasound contrast agents that can potentially access the extravascular space and be modified for molecular targeting. The purpose of the present study is to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 44 publications
(49 reference statements)
1
6
0
Order By: Relevance
“…The apparent half-life of GVs in the liver, 20 min, is substantially longer than their circulation time and on a time scale consistent with lysosomal processing. To independently confirm liver uptake, we acquired fluorescence images of mouse organs excised 1 h after IV injection of GVs labeled with a far-red fluorescent dye (Figure f). In line with previous investigations of GV biodistribution, , the liver was the dominant organ for GV uptake, emitting 81.4% of collected photons. The lungs (7.8%) and spleen (5.5%) had minor roles in GV clearance, while the heart and kidneys had no discernible role.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The apparent half-life of GVs in the liver, 20 min, is substantially longer than their circulation time and on a time scale consistent with lysosomal processing. To independently confirm liver uptake, we acquired fluorescence images of mouse organs excised 1 h after IV injection of GVs labeled with a far-red fluorescent dye (Figure f). In line with previous investigations of GV biodistribution, , the liver was the dominant organ for GV uptake, emitting 81.4% of collected photons. The lungs (7.8%) and spleen (5.5%) had minor roles in GV clearance, while the heart and kidneys had no discernible role.…”
Section: Resultssupporting
confidence: 90%
“…On the basis of their nanoscale dimensions and all-protein composition, which distinguishes them from other classes of ultrasound contrast agents, we hypothesized that we could use GVs as a contrast agent to noninvasively visualize the phagocytic and lysosomal functions of hepatic macrophages in vivo . Previous studies have shown that intravenously injected GVs are rapidly taken up by the liver. , If this uptake is mediated by macrophages and the internalized GVs undergo lysosomal proteolysis, this would manifest in the initial transfer of ultrasound contrast from the bloodstream to the liver, followed by its elimination with kinetics representative of natural RES clearance and degradation. Measurement of these processes would thus provide a quantitative picture of the complete phagocytic and lysosomal degradation pathways.…”
mentioning
confidence: 99%
“…In addition, mechanical cavitation of GVs using focused ultrasound has recently been shown to mediate potent cell-killing effects, illustrating another therapeutic approach for GVs 11 . Native GVs are rapidly cleared from circulation 12 and pegylation of GVs has recently been reported to enhance tumor contrast imaging in vivo 10 . Combined with their facile production, inherent resilience to a range of pH and temperature conditions, and lack of toxicity, such properties present GVs as a versatile and favorable nanoparticle platform to investigate for drug delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Building on this initial discovery, several other studies have been undertaken to understand the acoustic properties of GVs [9], to engineer them through genetic and biochemical modifications [10,11] (*ref. 10), to devise ultrasound imaging techniques tailored to distinguish their signal from background [12], and to characterize their in vivo biodistribution as purified, injectable agents [13]. These studies revealed remarkable non-linear acoustic properties and engineering versatility, enabling selective detection, multiplexed imaging and molecular targeting.…”
Section: Proteins With Air: Gas Vesicles As Acoustic Reporter Genesmentioning
confidence: 99%